Comparative geospatial and statistical analysis of DEM-derived geomorphic indices from multiple datasets for assessing relative active tectonics - Ahmed Gad; Heba El-Bagoury; Alaa Ahmed; Osman Abdelghany; Abdelnasser R. Abuzied (Geomatics, Natural Hazards & Risk)
Tectonic activity plays a vital role in achieving sustainable land management and hazard mitigation in seismically active regions. This study evaluates geomorphic indices derived from four digital elevation models (DEMs), including SRTM, Copernicus, FAB, and ALOS DEMs, to assess their influence on interpreting tectonic activity in the Wadi Araba basin. Six geomorphic indices, i.e. the hypsometric integral, stream length gradient, asymmetry factor, mountain front sinuosity, valley floor width to valley height ratio, and drainage basin shape, were integrated into a single Index of Relative Active Tectonics (IRAT) across sub-basins. The comparative analysis of multiple DEM datasets highlights the critical role of resolution and data quality in tectonic assessments, demonstrating that the ALOS DEM, with its 12.5-m resolution, captures finer details than 30-m DEMs (SRTM, Copernicus, and FAB DEMs), making it more suitable for applications requiring high sensitivity. However, the FAB DEM provides an acceptable balance of detail and smoothness, making it effective for general topographic studies while providing higher sensitivity than the SRTM and Copernicus DEMs. Hierarchical cluster analysis reveals the relationships between geomorphic indices and IRAT, emphasizing the impact of DEM selection on tectonic interpretation. The findings highlight the importance of using high-resolution DEM datasets in geomorphological and tectonic investigations to promote sustainability in the face of natural hazards.